THE EFFECT OF CALORIES COUNSELING ON INCREASE THE KNOWLEDGE, ATTITUDE, AND BEHAVIOR DIETARY TO DIABETES MELLITUS PATIENT IN PRIMARY HEALTH CARE - Setyoadi Setyoadi; Nanda Veir Yursyidah; Mifetika Lukitasari (Universitas Brawijaya, 2021)
Diabetes Mellitus (DM) is a metabolic disease with hyperglycemia because of abnormalities of insulin. Prevalence of DM increases from year to year and is predicted by 2030 to increase to 366 million. One of the efforts that can be done to reduce the high number of patients with DM is a group of calories counseling to solve the diet problems so that they can control the blood glucose levels. The purpose of this study was to determine the effect of calorie counseling on increasing knowledge, attitude, and behavior of patient dietary with DM in Semanding, Puskesmas Dau, Kabupaten Malang. The method used in this research is quasi-experimental design, a non-randomized pre-posttest control group. The samples were selected into two groups, that is the